Major trauma associated with mobility scooters: An analysis of the trauma audit research network. Issue 9 (September 2022) - Krahelski, O; Sivarajah, S; Eardley, W; Smith, TO; Hing, CB
Highlights: 10.6% of mobility scooter incidents on the TARN database resulted in mortality. The mortality rate was 15.4% of those who were over the age of 75 years and 24.2% in those who sustained major trauma. Patients over 75 years had similar ISS scores to those younger than 75 years, although had an increased mortality rate and increased length of stay in hospital. Limb injury was most common with more than half of patients sustaining an injury to the limb. However, head trauma was most closely associated with major trauma and mortality. Vehicle collisions accounted for almost two thirds of injuries and were the most dangerous mechanism of injury. The incidence of death following mobility scooter incidents is 1.66 times higher compared to incidents involving all registered vehicles in the UK. Abstract: Aims: To establish the incidence and nature of injuries seen in patients following mobility scooter incidents. Methods: The Trauma Audit and Research Network (TARN) database was used to collect data concerning injuries associated with mobility scooters. The data was taken from incidents that occurred between February 2014 and November 2020. The data analysed included: patient demographics, injury mechanism and patterns and associated mortality rates. Results: 1, 504 patients were identified of which 61.4% were male. The median age was 76.2 years (IQR 63.5–84.9). The median injury severity score (ISS) was 9 (IQR 9–17), with major trauma (ISS ≥16) being observed in 29.4% of patients. Injuries to the limb were most common, although injuries to the head were most severe. Vehicle collisions accounted for 65.4% of injuries and were most closely associated with the most severe incidents. The median length of stay in hospital was 12 days, excluding the patients who died. Overall, mortality following injury was 10.6%, but the mortality rate was 15.4% in those aged 75 years and over, and 24.2% in those sustaining severe trauma. Conclusion: As the population ages, injury characteristics of those with both major and non-major trauma changes. Mobility scooter use is prevalent amongst older people, and we provided a detailed analysis of injuries sustained with their use across a national database. The length of stay and the inherent resource use, because of admission following mobility scooter trauma, is considerable. These injuries particularly affect the 'most elderly' and carry a considerable mortality burden.